MUSCLE FIBER COMPOSITION OF THE HUMAN VOCAL MUSCLE: FREQUENCIES OF MUSCLE FIBER TYPES - SHIRAISHI, Naoki; SHIRAISHI, Yoko; NAGAI, Mayumi; INOKUCHI, Seiichiro; KIMURA, Tadanao (Journal of The Showa Medical Association, 2000)
The number of muscle fibers per 1 mm2 of unit area was obtained by scanning 100 points distributed evenly on a cross-sectional surface of the thyroarytenoid muscles including the vocal muscle ; the mean number of 25 subjects (14 males and 11 females) was 639.8±48.6. As for frequencies of muscle fiber types which are classified according to contraction functions, the mean frequency of red muscle fibers (Type I ) involved in sustaining tonic contraction and postural maintenance was the highest, 43.7%, followed by 28.8% for intermediate muscle fibers (Type III) which has a sarcoplasm between Types I and II (white muscle fibers involved in fast and twitch movements) and 27.6% for Type II, in that order. There was no statistically significant difference between Types II and III . The frequencies of Type I, II and III were not different between the three age groups (60, 70, 80 and above) and sex difference. A comparison of the thyroarytenoid muscle with the anterior tibial muscle of the leg as well show that the frequency of Type I was high. These results showed that the thyroarytenoid muscles including the vocal muscle, which is involved in phonation in humans, show a marked trend toward Type I.